2002
DOI: 10.1093/oxfordjournals.molbev.a004186
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Pattern of Mutation at Microsatellite Loci in Maize

Abstract: Microsatellites are important tools for plant breeding, genetics, and evolution, but few studies have analyzed their mutation pattern in plants. In this study, we estimated the mutation rate for 142 microsatellite loci in maize (Zea mays subsp. mays) in two different experiments of mutation accumulation. The mutation rate per generation was estimated to be 7.7 x 10(-4) for microsatellites with dinucleotide repeat motifs, with a 95% confidence interval from 5.2 x 10(-4) to 1.1 x 10(-3). For microsatellites with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
191
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(211 citation statements)
references
References 45 publications
12
191
1
3
Order By: Relevance
“…Another reason is that the high portion of trinucleotide repeats in coding regions may be due to the exertion of selection pressure for selecting particular single amino acid stretches (Morgante et al 2002). Also the most informative SSRs contained C10 repeats which are in agreement with the previous studies (Vigouroux et al 2002;Qureshi et al 2004;Kantartzi et al 2009). It was also observed that position of the SSR loci on the chromosome has no effect on the corresponding PIC values (Lacape et al 2003(Lacape et al , 2007.…”
Section: Genetic Characterizationsupporting
confidence: 87%
See 1 more Smart Citation
“…Another reason is that the high portion of trinucleotide repeats in coding regions may be due to the exertion of selection pressure for selecting particular single amino acid stretches (Morgante et al 2002). Also the most informative SSRs contained C10 repeats which are in agreement with the previous studies (Vigouroux et al 2002;Qureshi et al 2004;Kantartzi et al 2009). It was also observed that position of the SSR loci on the chromosome has no effect on the corresponding PIC values (Lacape et al 2003(Lacape et al , 2007.…”
Section: Genetic Characterizationsupporting
confidence: 87%
“…Most diploid species were wild except A-genome species. Wild species were not domesticated suggesting selection pressure for accumulating particular type of alleles was not applied is the reason for escalation in PIC values (Vigouroux et al 2002;Qureshi et al 2004). …”
Section: Microsatellite Polymorphismmentioning
confidence: 99%
“…The long-term effective population size (Ne) was obtained by assuming Long-term effective population size (Ne) was estimated by assuming the average mutation rate of the microsatellites in cobia to be 1 9 10 -4 mutation/generation/locus. The number of immigrants per generation (Nm) was estimated by multiplying h by M divided by 4 a Migration from the other sample group Aquacult Int (2013) 21: 197-217 209 the average mutation rate of the microsatellites in cobia to be 1 9 10 -4 mutation/generation/locus (Schug et al 1997;Vigouroux et al 2002;Whittaker et al 2003;Yue et al 2007). The number of immigrants per generation (Nm) was estimated by multiplying h by M divided by 4.…”
Section: Effective Population Size and Gene Flowmentioning
confidence: 99%
“…Mutation has virtually no effect at normal rates, but when the rate is 10 À3 , spatial autocorrelations at the smallest distances are decreased by an average of seven percent. The critical range, of 10 À2 down to 10 À3 , is spanned by microsatellite loci in animals (eg Bruford et al, 1992;Jarne and Lagoda, 1996) and plants (Udupa and Baum, 2001;Thuillet et al, 2002;Vigouroux et al, 2002), as well as some other hypervariable markers. For loci with more than a few alleles, mutation at a rate of 10 À2 causes 30-40% reductions in values for the finest scale autocorrelation.…”
Section: Choice Of Markersmentioning
confidence: 99%